Proposed Strategy of Internal Recruitment within The Coal Mining Industry (Case Study at PT Berau Coal) (The Indonesian Journal of Business Administration, 2021)
Berau Coal founded in 1983 as a company that produces coal in the East Kalimantan area. In the Covid-19 pandemic situation, the management of the company issued a policy not to recruit new employees from external company candidates, which means that the existing vacant positions can only be filled by recruitment from internal employees of the company. The difficulty of the HR Department in filling vacant positions is crucial where this will have an impact on the achievement of coal production. The purpose of this study is to provide recommendations regarding the recruitment strategy for the company in accordance with existing conditions in the company. The research methodology used is quantitative data, by distributing questionnaires to PT Berau Coal employees. Based on the results of the study, all independent variables showed a significant influence on the dependent variable. The results of the analysis also show that there are alternative solutions that companies can use to do internally branding for attracting their employees.Keywords: Employer Value Proposition, Employer Branding, Employer Attractiveness Intention toApply